2009
DOI: 10.1016/j.spl.2008.09.033
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate extremes of generalized skew-normal distributions

Abstract: We explore extremal properties of a family of skewed distributions extended from the multivariate normal distribution by introducing a skewing function π. We give sufficient conditions on the skewing function for the pairwise asymptotic independence to hold. We apply our results to a special case of the bivariate skew-normal distribution and finally support our conclusions by a simulation study which indicates that the rate of convergence is quite slow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…When a skew-normal random vector is considered, the resulting marginal maxima are still asymptotically independent, as has been shown by Lysenko et al [31] and Bortot [7]. Therefore some modifications, as provided by Hüsler and Reiss [23], are required in order to obtain a non-trivial limit.…”
Section: Multivariate Skew-t and Skew-normal Extreme-value Distributionsmentioning
confidence: 96%
See 2 more Smart Citations
“…When a skew-normal random vector is considered, the resulting marginal maxima are still asymptotically independent, as has been shown by Lysenko et al [31] and Bortot [7]. Therefore some modifications, as provided by Hüsler and Reiss [23], are required in order to obtain a non-trivial limit.…”
Section: Multivariate Skew-t and Skew-normal Extreme-value Distributionsmentioning
confidence: 96%
“…While the extremal behaviour of multivariate symmetric models such as the normal and t distributions has been extensively studied, their skewed versions have not been widely characterized. Attention to these skewed versions has only recently been paid by Chang and Genton [9], Lysenko et al [31] and Bortor [7]. The absence of the extremal versions of these models has motivated our interest in these families of distributions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2) is equal to the product of its marginal distributions (e.g Lysenko et al, 2009, Beirlant et al, 2004. However, Beranger et al (2017) showed that for the skew-normal case, the rate of convergence to zero of the upper-tail dependence function χ(u) in (4) depends on the slant parameters α, and depending on the sign of the elements of α, this can occur at a faster or slower rate than that of the normal case.…”
Section: Extremes Of Extended Skew-normal Random Samplesmentioning
confidence: 99%
“…, ξ m are linearly independent. Asymptotic independence of the skew-normal distribution has been partially proven in [17] using a direct analytic approach based on Sibuya's condition. Example 5.4.…”
Section: Examplesmentioning
confidence: 99%